STRUCTURING AN ACTIVITY THEORY-BASED FRAMEWORK FOR EVALUATING A SCIENCE EXTENDED CURRICULUM PROGRAMME. - Kizito, R. (South African Journal of Higher Education, 2015)
Determining the merits of programmes designed to increase the participation of under-prepared students in higher education is a complex undertaking. A dominant approach to programme evaluation focuses on the effects of single variables on students' performance. While useful for understanding the impact of individual factors, this approach does not offer a holistic view of how activities and processes shape the learning environment. An approach that could address this concern is cultural-historical activity theory (CHAT). Within an activity system, a participant (subject) whose agency is the focus of the analysis, acts on and transforms an (object) producing an outcome through mediating influences of other factors, such as community, division of labour and rules. This article reviews a selection of empirical studies using activity theory-based analysis. From this review, tenets of contemporary versions of activity theory (AT) are explicated, illustrating areas of compatibility and incongruities with evaluation practices. A way of coimbricating these approaches to develop a methodological framework for analysing the science extended curriculum programme (ECP) at the University of the Western Cape (UWC), Bellville, South Africa, and for future evaluation work, is proposed.